ANALISIS PROFITABILITAS USAHA PENGOLAHAN TRADISIONAL IKAN TONGKOL ASAP DI DESA JANGKAR KABUPATEN SITUBONDO - Ika Junianingsih (Faculty of Science and Technology University Ibrahimy, 2013)
This study was conducted to determine and analyze the profitability of the business value processing smoked swordfish. Profitability analysis effort is made to measure how effective / efficient an attempt to make a profit by using resources (resources) that exist. The research was conducted from August to October 2012, with research sites in the Village Anchor, Situbondo. Stages of research conducted through direct interviews (depth interview) to key persons (processors), using a semi-structured questionnaire, followed by fumigation business financial feasibility studies. Test methods for the analysis of profitability fumigation is done by calculating the value of profits, the ratio of R/C, and the ROI. The results showed that the capital used by a smoked tuna fish processing business is Rp. 409 967 550,-/year with receipts amounting to Rp. 540 000 000,-/year and profits of Rp. 130 032 450,-/ year. The result of the calculation of the ratio of R/C at 1,31/year showed that smoked tuna fish processing business that is efficient and well-deserved. As for the value ROI of 13.4%/year showed that smoked tuna fish processing business profitable to continue to be developed. Smoked tuna fish processing based on local wisdom in the village Anchor, Situbondo has the potential to be maintained as one of processed fishery products are worth and provide benefits to increased prosperity Situbondo that its presence needs to be maintained.